Repair material and repair method for electronic product shell

By using repair materials with components such as modified abrasives and aqueous epoxy resins, the problem that the machinability of existing repair materials strongly affects the photonity is solved, and efficient repair is achieved and the photonity and adhesion of the material surface is improved.

CN119823655APending Publication Date: 2025-04-15LIANHUIKE (SUZHOU) TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510059013.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15

Smart Images

  • Figure CN119823655A_ABST
    Figure CN119823655A_ABST
Patent Text Reader

Abstract

The invention discloses a repairing material and a repairing method for an electronic product shell, and belongs to the technical field of material polishing and repairing. The repair material for the electronic product shell comprises the following components in percentage by mass: 20%-30% of a modified abrasive material, 30%-40% of waterborne epoxy resin, 1%-2% of aluminum triphosphate, 10%-20% of ionic liquid, 0.5%-1% of a thickening agent, 0.5%-1% of a surfactant, 15%-20% of a lubricant and 0.5%-1% of an antioxidant. By adopting the repairing material and the repairing method for the electronic product shell, the problem that the surface smoothness of the repaired material is affected due to the fact that an existing repairing material is high in machinability can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material polishing and repairing, and in particular to a repairing material and a repairing method for an electronic product shell. Background Art

[0002] The shell of electronic products is generally made of aluminum alloy or plastic. Since aluminum alloy and plastic are relatively soft, scratches are easily generated on the surface of the electronic product shell during use, affecting the aesthetics of the electronic product. The existing scratch repair method is mainly modified by polishing. The existing polishing liquid only removes the surface of the material by polishing, exposing new material, and achieving the purpose of scratch repair. This method of repair is only suitable for repairing shallow scratches, and the repair efficiency is relatively low for large-area scratches.

[0003] The existing patent 202110985529.3 discloses an anodized film scratch repair liquid, comprising the following components: 15-40 parts of aluminum oxide, 15-40 parts of solvent, 10-30 parts of lubricant, 1-5 parts of thickener, and 7-13 parts of petroleum spirit. The above-mentioned anodized film scratch repair liquid, through the compatibility of multiple components, has the advantages of good adhesion and good gap filling performance, which can greatly reduce the time taken for repair and improve the repair efficiency. The workpiece after filling has high durability, and the filling performance under high temperature, high pressure and high humidity environment is still stable. The effect of repairing three injuries is excellent and will not modify the characteristics of the product itself. However, the above-mentioned patent mainly fills and polishes scratches with aluminum oxide. Aluminum oxide has a relatively high hardness and strong cutting properties on materials, which affects the smoothness of the surface of the material after repair. Summary of the invention

[0004] The purpose of the present invention is to provide a repair material and a repair method for an electronic product housing, so as to solve the problem that the existing repair material has strong cutting property and affects the surface finish of the repaired material.

[0005] To achieve the above-mentioned purpose, the present invention provides a repair material for an electronic product housing, characterized in that it comprises the following components in percentage by mass: 20%-30% of modified abrasive, 30%-40% of water-based epoxy resin, 1%-2% of aluminum tripolyphosphate, 10%-20% of ionic liquid, 0.5%-1% of thickener, 0.5%-1% of surfactant, 15%-20% of lubricant and 0.5%-1% of antioxidant.

[0006] Preferably, the modified abrasive is a mixture of modified silica and modified alumina.

[0007] Preferably, the mass ratio of the modified silicon dioxide to the modified aluminum oxide is 2-3:4, the particle size of the modified aluminum oxide is 120nm-150nm, and the particle size of the modified silicon dioxide is 200nm-300nm.

[0008] Preferably, the ionic liquid is an organic cationic ionic liquid.

[0009] Preferably, the surfactant is a nonionic surfactant, and the lubricant is glycerol.

[0010] The method for repairing the electronic product housing using the above-mentioned electronic product housing repair material comprises the following steps: S1. preparing modified abrasive; S2, adding the modified abrasive, aluminum tripolyphosphate, ionic liquid, surfactant and lubricant to the waterborne epoxy resin and stirring evenly; stirring for 40-60 minutes at a stirring speed of 100-200 rpm; S3, adding a thickener and an antioxidant, stirring for 20-30 minutes to obtain a repair material; S4. Clean the scratches on the outer shell of electronic products with water or alcohol; S5. Apply the repair material to the scratch, use a sponge wheel to evenly spread the repair material on the scratch, and fill the repair material inside the scratch; S6. After the repair material is dry, polish and grind the scratched surface to complete the repair.

[0011] Preferably, in S1, the method for preparing the modified abrasive comprises the following steps: S11, adding nano titanium dioxide powder to the methyl acrylate solution, stirring evenly at room temperature to obtain a mixed solution, rotating speed 200-300 rpm, stirring time 30-60 minutes.

[0012] S12, adding alumina powder and silicon dioxide powder to the mixed solution, adding N, N, N-trimethylammonium acrylate monomer and vinyl triethoxysilane coupling agent to the solution, heating the mixed solution in a water bath at 60-80° C., stirring, and reacting for 4-6 hours; S13, after the reaction is completed, the product is fully dried to obtain modified alumina and modified silica; the modified alumina and modified silica are ball-milled to obtain modified abrasives. The ball-milling speed is 300-400 rpm, and the ball-milling time is 2-4 hours.

[0013] Preferably, in S11, the particle size of the nano titanium dioxide powder is 10 nm-20 nm, and the nano titanium dioxide powder is 5%-10% of the mass of the methyl acrylate.

[0014] Preferably, in S12, the particle size of the aluminum oxide powder is 100nm-120nm, and the particle size of the silicon dioxide powder is 150nm-250nm; the aluminum oxide powder and the silicon dioxide powder are 10%-20% of the mass of the methyl acrylate.

[0015] Preferably, in S12, the N,N,N-trimethylammonium methyl acrylate monomer is 8%-10% of the mass of methyl acrylate.

[0016] The advantages and positive effects of the repair material and repair method for the electronic product housing of the present invention are: 1. The modified abrasive is a mixture of modified silica and modified alumina. The hardness of silica is moderate, while the hardness of alumina is relatively hard. Silica and alumina are mixed, and the particle size of alumina is limited to be smaller than that of silica, so that silica can buffer the cutting effect of alumina on the material surface, thereby reducing damage to the material surface while ensuring the polishing efficiency of the material.

[0017] 2. Negatively charged ionized acrylic resin is wrapped around the outside of alumina powder and silica powder to protect the alumina and silica powder, reduce damage to the outer shell of electronic products, and help improve polishing efficiency.

[0018] 3. Nano titanium dioxide powder is distributed on the surface or inside of the resin. The surface of the shell is fully polished by the titanium dioxide powder, which improves the polishing efficiency and polishing effect.

[0019] 4. The ionic liquid is an organic cationic ionic liquid, and the uniformity of the dispersion of the modified abrasive in the repair material is improved under the action of anions and cations.

[0020] 5. Waterborne epoxy resin has a buffering effect on the modified abrasive, and the waterborne epoxy resin increases the viscosity of the filling material, reduces the sedimentation of the modified abrasive in the filling material, and improves the uniformity of the modified abrasive dispersion. Aluminum tripolyphosphate can react with the hydroxyl and epoxy groups in the waterborne epoxy resin to improve the adhesion of the repair material on the shell.

[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a repair flow chart of an embodiment of the present invention; Figure 2 This is a schematic diagram of the electronic product housing before repair; Figure 3 This is a schematic diagram of the electronic product housing after being repaired using the filling material described in Example 2. DETAILED DESCRIPTION

[0023] In this application, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application. In the event of any inconsistency, the meaning described in this specification or the meaning derived from the contents recorded in this specification shall prevail. In addition, the terms used herein are only for the purpose of describing the embodiments of the present application and are not intended to limit the present application. In order to accurately describe the technical content in this application and to accurately understand the present invention, the following explanations or definitions are given to the terms used in this specification before describing the specific embodiments: The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings.

[0024] A repair material for an electronic product housing comprises the following components in percentage by mass: 20%-30% of modified abrasive, 30%-40% of waterborne epoxy resin, 1-2% of aluminum tripolyphosphate, 10-20% of ionic liquid, 0.5-1% of thickener, 0.5-1% of surfactant, 15-20% of lubricant and 0.5-1% of antioxidant.

[0025] The modified abrasive is a mixture of modified silica and modified alumina.

[0026] The mass ratio of modified silicon dioxide to modified aluminum oxide is 2-3:4, the particle size of modified aluminum oxide is 120-150 nm, and the particle size of modified silicon dioxide is 200-300 nm.

[0027] The hardness of silicon dioxide is moderate, while the hardness of aluminum oxide is relatively hard. Silicon dioxide and aluminum oxide are mixed, and the particle size of aluminum oxide is limited to be smaller than that of silicon dioxide, so that silicon dioxide can buffer the cutting effect of aluminum oxide on the material surface, thereby ensuring the polishing efficiency of the material and reducing the damage to the material surface.

[0028] Ionic liquids are organic cationic ionic liquids.

[0029] The surfactant is a nonionic surfactant and the lubricant is glycerol.

[0030] like Figure 1 The electronic product housing repair method includes the following steps: S1. Prepare modified abrasive.

[0031] The preparation method of the modified abrasive comprises the following steps: S11. Add nano titanium dioxide powder to the methyl acrylate solution, stir evenly at room temperature to obtain a mixed solution, rotate at 200 rpm to 300 rpm, and stir for 30 minutes to 60 minutes.

[0032] The particle size of the nano titanium dioxide powder is 10nm-20nm, and the mass of the nano titanium dioxide powder is 5%-10% of the mass of the methyl acrylate.

[0033] S12. Add alumina powder and silica powder to the mixed solution, add N,N,N-trimethylammonium acrylate monomer and vinyl triethoxysilane coupling agent to the solution, heat the mixed solution in a water bath at 60-80°C, stir, and react for 4-6 hours.

[0034] The particle size of the aluminum oxide powder is 100nm-120nm, and the particle size of the silicon dioxide powder is 150nm-250nm; the aluminum oxide powder and the silicon dioxide powder are 10%-20% of the mass of the methyl acrylate.

[0035] The N, N, N-trimethylammonium acrylate monomer is 8%-10% of the mass of methyl acrylate.

[0036] N, N, N-trimethylammonium acrylate monomer and methyl acrylate polymerize to generate an ionized acrylic resin with a negative charge on the surface, which is wrapped around the outside of the aluminum oxide powder and the silicon dioxide powder to protect the aluminum oxide and silicon dioxide powder, reduce damage to the electronic product shell, and help improve the polishing efficiency. Nano titanium dioxide powder is distributed on the surface or inside of the resin, and the surface of the shell is fully polished by titanium dioxide powder, which improves the polishing efficiency and polishing effect. When titanium dioxide, aluminum oxide, and silicon dioxide are used to fill the scratches on the shell, they can increase the hardness of the filling material and improve the glossiness of the filling material.

[0037] S13, after the reaction is completed, the product is fully dried to obtain modified alumina and modified silica. The modified alumina and modified silica are ball-milled to obtain modified abrasives. The ball-milling speed is 300-400 rpm, and the ball-milling time is 2-4 hours.

[0038] S2. Add the modified abrasive, aluminum tripolyphosphate, ionic liquid, surfactant and lubricant into the waterborne epoxy resin and stir evenly; stir for 40-60 minutes at a stirring speed of 100 rpm-200 rpm.

[0039] The waterborne epoxy resin has a buffering effect on the modified abrasive, and the waterborne epoxy resin increases the viscosity of the filling material, reduces the sedimentation of the modified abrasive in the filling material, and improves the uniformity of the modified abrasive dispersion. The surface of the modified abrasive is coated with negatively charged ionized acrylic resin, which improves the uniformity of the modified abrasive dispersion in the repair material under the action of anions and cations in the organic cationic ionic liquid.

[0040] Aluminum tripolyphosphate can undergo a complex reaction with the hydroxyl and epoxy groups in the water-based epoxy resin, thereby improving the adhesion of the repair material to the shell, improving the bonding strength between the repair material and the shell, and improving the repair effect on the scratches on the shell.

[0041] S3. Add a thickener and an antioxidant, stir for 20-30 minutes, and obtain a repair material.

[0042] S4. Clean the scratches on the outer shell of electronic products with water or alcohol.

[0043] S5. Apply the repair material to the scratch, use a sponge wheel to spread the repair material evenly on the scratch, and fill the repair material inside the scratch.

[0044] S6. After the repair material is dry, use silicon carbide polishing liquid to polish the scratched surface to complete the repair.

[0045] Example 1 A repair material for an electronic product housing comprises the following components in percentage by mass: 30% of modified abrasive, 30% of waterborne epoxy resin, 1% of aluminum tripolyphosphate, 20% of ionic liquid, 1% of thickener, 0.8% of surfactant, 15.5% of lubricant and 0.7% of antioxidant.

[0046] The mass ratio of modified silica to modified alumina is 2:4, the particle size of modified alumina is 130 nm, and the particle size of modified silica is 200 nm.

[0047] Ionic liquids are organic cationic ionic liquids.

[0048] The surfactant is a polydimethylsiloxane surfactant, the lubricant is glycerin, the antioxidant is tert-butylhydroquinone, and the thickener is ethyl hydroxyethyl cellulose.

[0049] The particle size of the nano titanium dioxide powder is 10nm-20nm, and the nano titanium dioxide powder is 10% of the mass of the methyl acrylate.

[0050] The particle size of the aluminum oxide powder is 100 nm, and the particle size of the silicon dioxide powder is 150 nm; the aluminum oxide powder and the silicon dioxide powder are 20% of the mass of the methyl acrylate.

[0051] Example 2 A repair material for an electronic product housing comprises the following components in percentage by mass: 26% of modified abrasive, 35% of waterborne epoxy resin, 2% of aluminum tripolyphosphate, 15% of ionic liquid, 1% of thickener, 1% of surfactant, 19% of lubricant and 1% of antioxidant.

[0052] The mass ratio of modified silica to modified alumina is 3:4, the particle size of modified alumina is 130 nm, and the particle size of modified silica is 260 nm.

[0053] Ionic liquids are organic cationic ionic liquids.

[0054] The surfactant is a polydimethylsiloxane surfactant, the lubricant is glycerin, the antioxidant is tert-butylhydroquinone, and the thickener is ethyl hydroxyethyl cellulose.

[0055] The particle size of the nano titanium dioxide powder is 10nm-20nm, and the nano titanium dioxide powder is 8% of the mass of methyl acrylate.

[0056] The particle size of the aluminum oxide powder is 100 nm, and the particle size of the silicon dioxide powder is 230 nm; the aluminum oxide powder and the silicon dioxide powder are 16% of the mass of the methyl acrylate.

[0057] Example 3 A repair material for an electronic product housing comprises the following components in percentage by mass: 23% modified abrasive, 38% waterborne epoxy resin, 2% aluminum tripolyphosphate, 20% ionic liquid, 0.8% thickener, 0.6% surfactant, 15% lubricant and 0.6% antioxidant.

[0058] The mass ratio of modified silica to modified alumina is 2:4, the particle size of modified alumina is 150 nm, and the particle size of modified silica is 300 nm.

[0059] Ionic liquids are organic cationic ionic liquids.

[0060] The surfactant is a polydimethylsiloxane surfactant, the lubricant is glycerin, the antioxidant is tert-butylhydroquinone, and the thickener is ethyl hydroxyethyl cellulose.

[0061] The particle size of the nano titanium dioxide powder is 10nm-20nm, and the nano titanium dioxide powder is 10% of the mass of the methyl acrylate.

[0062] The particle size of the aluminum oxide powder is 120 nm, and the particle size of the silicon dioxide powder is 250 nm. The aluminum oxide powder and the silicon dioxide powder are 20% of the mass of the methyl acrylate.

[0063] Performance Test: The filler materials described in Examples 1-3 were used to repair the scratches on the housing of electronic products made of aluminum alloy and ABS plastic, and the repaired surface was macroscopically observed. The repaired surface was measured using a gloss meter and a surface roughness tester. The results are shown in Table 1.

[0064] The repair material described in Example 2 is used to repair the scratches on the electronic product housing made of aluminum alloy. Figure 2 As shown, the effect after repair is as follows Figure 3 As shown. Figure 2 and Figure 3 It can be seen that no scratches can be seen on the repaired shell from a macroscopic perspective, which shows a very good macroscopic repair effect.

[0065] It can be seen from Table 1 that the repair material of the present invention has a very good repair effect on scratches on electronic product shells made of metal and plastic materials.

[0066] Therefore, the use of the repair material and the repair method for the electronic product housing of the present invention can solve the problem that the existing repair material has strong cutting properties and affects the surface finish of the repaired material.

[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A repair material for an electronic product housing, characterized in that: The invention comprises the following ingredients in percentage by weight: 20%-30% of modified abrasive, 30%-40% of waterborne epoxy resin, 1%-2% of aluminum tripolyphosphate, 10%-20% of ionic liquid, 0.5%-1% of thickener, 0.5%-1% of surfactant, 15%-20% of lubricant and 0.5%-1% of antioxidant.

2. The repair material for an electronic product housing according to claim 1, characterized in that: The modified abrasive is a mixture of modified silicon dioxide and modified aluminum oxide.

3. The repair material for an electronic product housing according to claim 2, characterized in that: The mass ratio of the modified silicon dioxide to the modified aluminum oxide is 2-3:4, the particle size of the modified aluminum oxide is 120nm-150nm, and the particle size of the modified silicon dioxide is 200nm-300nm.

4. The repair material for an electronic product housing according to claim 1, characterized in that: The ionic liquid is an organic cationic ionic liquid.

5. The repair material for an electronic product housing according to claim 1, characterized in that: The surfactant is a nonionic surfactant, and the lubricant is glycerol.

6. A method for repairing an electronic product housing using the electronic product housing repair material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. preparing modified abrasive; S2, adding the modified abrasive, aluminum tripolyphosphate, ionic liquid, surfactant and lubricant to the waterborne epoxy resin and stirring evenly; stirring for 40-60 minutes at a stirring speed of 100 rpm-200 rpm; S3, adding a thickener and an antioxidant, stirring for 20-30 minutes to obtain a repair material; S4. Clean the scratches on the outer shell of electronic products with water or alcohol; S5. Apply the repair material to the scratch, use a sponge wheel to evenly spread the repair material on the scratch, and fill the repair material inside the scratch; S6. After the repair material is dry, polish and grind the scratched surface to complete the repair.

7. The method for repairing an electronic product housing using a repair material for an electronic product housing according to claim 6, characterized in that: In S1, the preparation method of the modified abrasive comprises the following steps: S11, adding nano titanium dioxide powder to the methyl acrylate solution, stirring evenly at room temperature to obtain a mixed solution, rotating speed 200 rpm-300 rpm, stirring time 30-60 minutes; S12, adding alumina powder and silica powder to the mixed solution, adding N, N, N-trimethylammonium acrylate monomer and vinyl triethoxysilane coupling agent to the solution, heating the mixed solution in a water bath at 60° C.-80° C., stirring, and reacting for 4-6 hours; S13, after the reaction is completed, the product is fully dried to obtain modified alumina and modified silica; the modified alumina and modified silica are ball-milled to obtain modified abrasives. The ball-milling speed is 300 rpm-400 rpm, and the ball-milling time is 2-4 hours.

8. The method for repairing an electronic product housing using a repair material for an electronic product housing according to claim 7, characterized in that: In the S11, the particle size of the nano titanium dioxide powder is 10nm-20nm, and the nano titanium dioxide powder is 5%-10% of the mass of the methyl acrylate.

9. The method for repairing an electronic product housing using a repair material for an electronic product housing according to claim 7, characterized in that: In the S12, the particle size of the aluminum oxide powder is 100nm-120nm, and the particle size of the silicon dioxide powder is 150nm-250nm; the aluminum oxide powder and the silicon dioxide powder are 10%-20% of the mass of the methyl acrylate.

10. The method for repairing an electronic product housing using a repair material for an electronic product housing according to claim 7, characterized in that: In the S12, the N,N,N-trimethylammonium methyl acrylate monomer is 8%-10% of the mass of methyl acrylate.

Citation Information

Patent Citations

  • Anodic oxide film scratch repair liquid

    CN113737248A